Uso de corante natural em embalagens biodegradáveis: avaliação da estabilidade em diferentes temperaturas de armazenamento e potencial de mercado - Baroni, Karine Camargo (2023)
The demand for sustainable practices drives ecologically correct alternatives in the production of packaging materials, both in the composition of the packaging and the dyes used in it. It is also strategic to know the positive market perception of packaging in this innovative approach. In this context, the objective of this study was to explore the technical feasibility and market potential of biodegradable cassava starch films improved by the addition of freeze-dried pine nut shell extract as a dye. The pine nut was chosen because it is part of the local economy and its extinction (shell) is a byproduct of the agro-industrial area. The study was divided into two stages. The first focuses on the production of pine nut shell extract, and the incorporation of 4% of cassava starch into a biodegradable film extruded by balloon blowing. The films were evaluated for mechanical properties, scanning electron microscopy, FTIR-ATR (Fourier Transform Infrared - Attenuated Total Reflectance), colorimetry, RGB - Red Green Blue, antioxidant potential FRAP (Ferric Reducing Antioxidant Power), DPPH (2 ,2-diphenyl-1-picrylhydrazyl) and antimicrobial since its manufacture and for 150 days in different ambient (25ºC), refrigerated (4ºC) and frozen (-18ºC) storage conditions every 30 days. In the second stage, three cashing films were made with extracts of pine nut shell, grape pomace and ora-pro-nobis leaves. Consumer perceptions regarding sustainable packaging were investigated and market potential was analyzed through the food choice and word association questionnaire. The results of the first study revealed the effect of temperature and time on the conservation of Biodegradable. The films with freeze-dried pine nut shell extract, compared to the control, showed better elongation and lower breaking strength, antioxidant action, dark coloring. The second study showed that health and ethical concerns had significantly low/weak positive effects on natural content, while weight control had a medium/positive effect on natural content. On the other hand, Humor was found to have a significant negative/medium effect on Natural Content. Natural content has a big effect on the importance consumers give to environmentally packaged foods The Word Association revealed a positive perception regarding the presentation of colored biodegradable packaging and a more positive perception, defined by happiness, when knowing that it is biodegradable packaging colored with natural dyes.